THE RESEARCH PROGRAM ON TEACHER ACTION, STUDENT ACTION AND THEIR CONNECTIONS (PROACTION): FUNDAMENTALS AND METHODOLOGICAL APPROACHES - Arruda, Sergio de Mello; Passos, Marinez Meneghello; Dias Broietti, Fabiele Cristiane (Revista de Produtos Educacionais e Pesquisas em Ensino, 2021)
This article deals with the theoretical foundations and methodological approaches of a Research Program, which has been under development for ten years, that investigates the actions of teachers and students by direct observation in the classroom. The Program received the name: The Research Program on Teacher Action, Student Action and their Connections (PROACTION) and has two general research questions: a) Which teacher and student actions are observed in science and mathematics classes in basic and higher education, how can they be interpreted and in what ways do they connect with each other? b) What implications for teaching, learning and teacher education can be drawn from the results found? In the article we present three possibilities of theoretical foundations for the Program, based on the articulation with teacher education, with the social theories of action and with the Actor-Network Theory. We also explain three different investigative approaches to address these questions: the first focuses on the description of the actions, the second on the explanation, and the third on the connections between the actions. At the end, we comment on the Program’s developments and some points to be explored in the future research.